The request - Bell, David, 1969 November 17- (Berkley, 2020)
"When a man agrees to do a favor for a friend, he gets more than he bargained for as he becomes embroiled in a woman's murder in this new thriller from the USA Today bestselling author of Layover. Ryan Francis has it all--great job, wonderful wife, beautiful child. That is until an old friend, Blake Norton, asks Ryan to help keep his affair a secret by retrieving an incriminating item from the woman's home. Ryan refuses to help, but when Blake threatens to reveal his deepest and darkest secret--which could put everything in Ryan's life in jeopardy--Ryan has no choice. When he arrives at the woman's house, Ryan is shocked to learn two things: he knows the woman Blake is having an affair with, and she is dead on her bedroom floor. With the sound of police sirens rapidly approaching, Ryan flees, wondering why his old friend was setting him up for murder. Determined to keep his life intact and to clear his name, Ryan can't rest until he finds out who the real murderer is--but solving the crime may lead him closer to home than he ever could have imagined"--